Dynamic Monopoly and Consumers Profiling Accuracy - Didier Laussel; Ngo Van Long; Joana Resende (Center for Economic Studies and ifo Institute (CESifo), 2021)
Using a Markov-perfect equilibrium model, we show that the use of customer data to practice intertemporal price discrimination will improve monopoly profit if and only if information precision is higher than a certain threshold level. This U-shaped relationship lends support to a popular view that knowledge is good only if it is sufficiently refined. When information accuracy can only be achieved through costly investment, we find that investing in profiling is profitable only if this allows to reach a high enough level of information precision. Consumers expected surplus being a hump-shaped function of information accuracy, we show that consumers have an incentive to lobby for privacy protection legislation which raises the cost of monopoly's investment in information accuracy. However, this cost should not dissuade firms to collect some information on customers' tastes, as the absence of consumers' profiling is actually detrimental to consumers.
Keywords: C73; D42; L12; L15; 330; consumers profiling; endogenous investment in profiling capability; dynamic monopoly; consumers` collective action on privacy protection legislation